Vascular considerations in autologous breast reconstruction using DIEP or MS-TRAM flaps: Standard techniques, alternatives, and rescue strategies - Promny, Theresa; Arkudas, Andreas; Huberth, Paula; Horch, Raymund E. (Innovative Surgical Science, 2025)
Microsurgical breast reconstruction is an established method following mastectomy; however, various factors significantly influence the complication rate. This analysis evaluates the impact of vascular anastomosis techniques, previous surgeries, and radiotherapy on the success rate of microsurgical breast reconstruction. In a retrospective data analysis of 396 patients who underwent 447 flap procedures (single or bilateral microsurgical breast reconstruction) using tissue from the lower abdomen (either DIEP or MS-TRAM flaps), the type of venous and arterial anastomoses, the initial findings or surgical specifics at the thoracic recipient site and their influence on complications were examined. Anastomosing two veins per flap did not result in a significant reduction of major complications. Flap loss was significantly more common when standard venous anastomosis to the internal mammary vein was not used, underscoring their role as the preferred recipient vessels. No major complications were observed in patients receiving a caudal anastomosis to the internal mammary artery. Patients with prior radiotherapy exhibited an increased need for arterial revisions. All documented seromas and infections occurred in irradiated patients. A differentiated surgical plan that considers optimal anastomosis techniques, supercharging strategies, and individual risk factors is crucial to reducing complications. Further studies are needed to optimize patient-specific strategies.
CRIS-Team Scopus Importer:2025-06-06
Keywords: complications; cross over bypass; flap revision; supercharging; turbocharging